Forest Restoration in an Abandoned Seasonally Dry Tropical Forest in the Mae Klong Watershed, Western Thailand - Ritthikai Saikhammoon; Sarawood Sungkaew; Sathid Thinkampaeng; Wongsatorn Phumphuang; Torlarp Kamyo; Dokrak Marod (Environment and Natural Resources Journal, 2023)
Deforestation for the development of agricultural land is a critical driver of biodiversity loss. We examined the relationships between tree species and environments after the abandonment of a plot of land at the Mae Klong Watershed Research Station, Western Thailand. Vegetation monitoring was conducted every two years on a 16-ha permanent plot established in 2011 until 2019. All trees with diameter at breast height (DBH)≤1 cm were measured. Canonical correspondence analysis (CCA) was performed to investigate the relationships between tree species and environments. We found a total of 199 tree species in the plot, which comprised both pioneer and climax species. The high tree density and low basal area were 1,280 stem/ha and 7.30 m2/ha, respectively. During 2011-2019, the species richness and total tree density were decreased by nine species (from 206 to 197 species) and 83 stem/ha (from 1,120 to 1,037 stem/ha). In contrast, the total basal area increased from 6.41 to 7.26 stem/ha. According to the measured environmental variables, mixed deciduous species such as Pterocarpus macrocarpus and Xylia xylocarpa var. kerrii preferred higher elevations and drier sites compared to dry evergreen species such as Dipterocarpus alatus. Early colonizing species such as Trema orientalis and Ficus species exhibited rapid population decreases, whereas climax species such as Lagerstroemia tomentosa exhibited highly successful regeneration under natural conditions. Artificial reforestation efforts may be required in areas with large disturbance, including the planting of mixed tree species to promote natural regeneration and reduce the recovery period.